Analysis Medical Logistics Management: A Case Study at the Pharmacy Installation of TK. III Dr. Shindu Trisno Hospital, Palu City - Azraaqin, Shakira Aniza; Miru, Sulaeman; Nugraha, Mohammad Ega; Hadi, Suryadi (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The management of medication logistics is a critical component of hospital operations, encompassing interconnected stages such as planning, procurement, receipt, storage, distribution, disposal, and control. This study aims to comprehensively describe the medication logistics management process, from planning to control, as an integral part of delivering high-quality healthcare services. Utilizing a descriptive qualitative research approach, the study was conducted at TK. III Dr. Sindhu Trisno Hospital in Palu. Data collection involved in-depth interviews and field observations, with informants comprising four key personnel: the Head of Pharmacy, Pharmacy Staff, Head of the Medication Warehouse, and the Warehouse Keeper. The findings revealed that medication planning is conducted using a consumption-based method, grounded in patient usage patterns. Medication procurement utilizes the Kanza application for real-time stock recording. Storage adheres to the FEFO (First Expired, First Out) method, ensuring medication safety and quality in compliance with standards. Distribution is prescription-based and closely monitored, while disposal follows procedures outlined in Ministry of Health Regulation No. 58 of 2014. Medication logistics control leverages an information system that facilitates rapid decision-making to prevent stock shortages or surpluses. This study highlights the importance of technology adoption, inter-unit coordination, and regulatory compliance in managing medication logistics to ensure optimal availability and quality healthcare services